STUDI KUALITATIF EKSPLORASI DAMPAK GAME ONLINE : MOBILE LEGENDS TERHADAP PERILAKU & EMOSI REMAJA DI KABUPATEN MINAHASA - Usoh, Trivena; Buanasari, Andi; Wowiling, Ferdinand (JURNAL KEPERAWATAN, 2024)
Background. Mobile Legends online games can have both positive and negative effects on all players. An unnatural or excessive dependence on online games can have a negative impact on a person's physical and psychological well-being. Aim. This study aims to explore how the impact of Mobile Legends games on the behavior and emotions of adolescents in Leilem Village, Sonder District, Minahasa Regency. Methods. This study used a qualitative research design with a phenomenological study approach. Data collection was done by in-depth interviews and observation. Sampling in this study used purposive sampling technique, with the number of participants being 12 people, namely 10 adolescents and 2 parents. Data analysis was carried out based on the steps according to Colaizzi. Results. In this study, 3 themes were obtained: 1) Factors causing addiction to the Mobile Legends game, 2) Changes due to playing the Mobile Legends game on adolescents in various aspects, 3) Parents' response to changes in adolescents due to playing the Mobile Legends game. Conclusion. Addiction to playing the Mobile Legends game in adolescents has an impact on various changes in the behavior and emotions of adolescents. Thus it is important to know the impact of online games so that an appropriate online game addiction treatment program can be created among adolescents. Keywords: Online gaming addiction; emotional changes; behavioral changes; adolescents